Investigation of modal analysis on glass fiber laminate aluminium reinforced polymer: An experimental study - M. N. M., Merzuki; M. R. M., Rejab; M. S. M., Sani; Zhang, Bo; Quanjin, Ma; Wan, Rafizi (IOP Publishing, 2019)
The present analysis deals with experimental investigation on the vibration behaviour of fiber metal laminates (FMLs) plate. FMLs offer good mechanical properties such as high specific properties in term of strength to weight and stiffness to weight ratio. However, it is observed that very few studies are available on the dynamic behaviour of FMLs. In this experiment, the dynamical behaviour of glass fiber/epoxy and fiber metal laminates was carried out. The specimens have been manufactured using different manufacturing process which is compression mould and vacuum bagging. Free vibration analysis by exciting an impact hammer at the cantilever plate were conducted to determine the dynamical characteristic of the specimens. The stiffness of the material increases, which contributes to the natural frequency increase.